Hygrothermal performance of building envelopes in the tropics under operative conditions: condensation and mould growth risk appraisal - Ali, Maisarah; Oladokun, Majeed Olaide; Osman, Samsul Bahrin; Mohd. Din, Shamzani Affendy; Ibrahim, Mohd Shariffuddin; Yusof, Faridah (Universiti Teknologi Malaysia, 2016)
Poor indoor hygrothermal performance increases the risk of indoor moisture problems and deterioration due to mould growth, corrosion and damage to archival materials. Hence,proper control of indoor thermohygric intensity abates indoor moisture and its associated problems. This paper presents the results of envelopes hygrothermal performance assessments in a hot and humid climate building with varying operational profile between adjacent spaces. The case-studied building runs on 24hrs cooling mode in one part against natural and/or mechanical supply-exhaust fan means on the other. In-situ experiments were combined with hygrothermal analytical methods to assess the envelope thermal quality together with the operative conditions against condensation and mould growth risks. The results show that the building is overcooled leading to poor envelope hygrothermal performance with associated condensation and mould growth problems on non-airconditioned sides of the envelopes.